Police reform in Ukraine. A reconnaissance of perceptions - Sviatokum, I. O.; Святокум, І. О.; ORCID: http://orcid.org/0000-0003-4374-5494; ResearcherID: I-7047-2016; Serdiuk, O. O.; Сердюк, О. О.; ORCID: http://orcid.org/0000-0002-5733-6432; ResearcherID: I-5924-2016; Scopus Author ID: 56857350300; Duyne, van Petrus C. (Constructing and organising crime in Europe / Petrus C. van Duyne, Alexey Serdyuk, Georgios A. Antonopoulos, Jackie H. Harvey, Klaus von Lampe (Eds.); Kharkiv National University of Internal Affairs, Northumbria University, Teesside University, Utrecht University. – Chicago-Kharkiv : Eleven International Publishing, Kharkiv National University of Internal Affairs, 2019. - P. 336-377, 2019)
Після проголошення незалежності в 1991 році Україна успадкувала стару радянську поліцейську систему, не вносячи істотних змін. По суті, структура залишилася на місці, і перший національний закон «Про міліцію», прийнятий в 1990 році, хоча технічно Україна була ще радянською республікою, нічого не змінив у тому, як працював старий, а потім і новий правоохоронний орган. Міліція продовжувала функціонувати як явно воєнізована, сильно централізована система при Міністерстві внутрішніх справ. Останні і перші були організаційно розділені, що означало, що міністерство одночасно служило центральним органом управління міліції, причому міністр був де-факто главою міліції (де-юре, відповідної посади навіть не існувало). Радянська спадщина також проявилося в способах вимірювання ефективності міліції. Оцінка ефективності грунтувалася головним чином на статистиці злочинності, вимірюючи такі показники, як кількість зареєстрованих злочинів, рівень розкриття, рівень засудження і т. Д. (Марковська та Сердюк, 2013). Показники поточного періоду порівнювалися з відповідними показниками за попередній період, тому необхідно або зберегти показники на колишньому рівні, або постійно «покращувати» їх, але в межах правдоподібного діапазону. Ця система створила сильні стимули для офіцерів маніпулювати цифрами для досягнення необхідних цілей і, таким чином, була спрямована на те, щоб представити громадськості упереджені цифри, що маніпулюють процес оцінки (Марковська та Сердюк, 2013). Першим важливим документом, що виражає серйозні наміри українського уряду з реформування міліції, є Постанова Кабінету Міністрів України про основи розвитку системи МВС в 1996 році. Документ не торкався вищезгаданих питань, але замість цього зосередив увагу на розвитку міліції в існуючих рамках. Пізніше питання реформування Міністерства внутрішніх справ та міліції періодично порушувалося (в 1996-1998 роках, в 2003 році, в 2005 році, в 2010 році і т. д.) І знову опускався. Хоча в деяких випадках деякі зміни дійсно були здійснені, міліція все ще в значній мірі зберігала свій централізований характер, засновану на планах оцінку ефективності та інші особливості, успадковані від радянського періоду. Ми не будемо намагатися детально аналізувати кожен з цих випадків; замість цього, в цьому розділі ми зосередимо нашу увагу на двох випадках реформ, а саме на спробу скасувати дорожню поліцію (ДАІ) в 2005 році і реформу кримінально-процесуального законодавства в 2012 році.

After proclaiming independence in 1991, Ukraine inherited the old Soviet police system without introducing significant changes. Basically, the structure remained in place, and the first national law “On militsiya”, adopted in 1990, while, technically, Ukraine was still a Soviet Republic, did not change anything in the ways the old and then new law enforcement body worked. The militsiya continued to function as a clearly militarised, heavily centralised system under the Ministry of Internal Affairs. The latter and the former were not organisationally separated, meaning that the ministry concurrently served as a central managing body of the militsiya, with the minister being de facto head of the militsiya (de jure, the relevant position did not even exist). The Soviet legacy also manifested itself in the way the performance of the militsiya was measured. Performance assessment was based primarily on the criminal statistics, measuring such indicators as number of registered crimes, clearance rate, conviction rate etc. (Markovska and Serdyuk, 2013). Indicators of the current period were compared to the relevant numbers from the previous period, making it necessary to either keep the indicators on the same level or to constantly “improve” them, but within a plausible range. This system created strong incentives for the officers to manipulate numbers in order to achieve required goals and, thus, was geared towards presenting the public with biased figures from a manipulated assessment process (Markovska and Serdyuk, 2013). The first major document expressing serious intentions of the Ukrainian government to reform the militsiya is the Resolution of the Cabinet of Ministers of Ukraine on the framework of development of the system of Ministry of Internal Affairs in 1996. The document did not address aforementioned issues, but focusing instead on the development of the militsiya within the existing framework. Later, the issue of reforming the Ministry of Internal Affairs and the militsiya had been periodically raised (in 1996-1998, in 2003, in 2005, in 2010 etc.) and dropped again. While in certain cases some changes have indeed been implemented, the militsiya still largely retained its centralised nature, plan-based performance assessment and other features inherited from the Soviet period. We will not attempt to analyse each of these instances in detail; instead, in this chapter we focus our attention on the two more publicised cases of reforms, namely, the attempt to abolish the traffic police (DAI) in 2005 and the reform of the criminal procedural law in 2012.

После провозглашения независимости в 1991 году Украина унаследовала старую советскую полицейскую систему, не внося существенных изменений. По сути, структура осталась на месте, и первый национальный закон «О милиции», принятый в 1990 году, хотя технически Украина была еще советской республикой, ничего не изменил в том, как работал старый, а затем и новый правоохранительный орган. Милиция продолжала функционировать как явно военизированная, сильно централизованная система при Министерстве внутренних дел. Последние и первые не были организационно разделены, что означало, что министерство одновременно служило центральным органом управления милиции, причем министр являлся де-факто главой милиции (де-юре, соответствующей должности даже не существовало). Советское наследие также проявилось в способах измерения эффективности милиции. Оценка эффективности основывалась главным образом на статистике преступности, измеряя такие показатели, как количество зарегистрированных преступлений, уровень раскрытия, уровень осуждения и т. Д. (Марковская и Сердюк, 2013). Показатели текущего периода сравнивались с соответствующими показателями за предыдущий период, поэтому необходимо либо сохранить показатели на прежнем уровне, либо постоянно «улучшать» их, но в пределах правдоподобного диапазона. Эта система создала сильные стимулы для офицеров манипулировать цифрами для достижения требуемых целей и, таким образом, была направлена ​​на то, чтобы представить общественности предвзятые цифры из манипулируемого процесса оценки (Марковска и Сердюк, 2013). Первым важным документом, выражающим серьезные намерения украинского правительства по реформированию милиции, является Постановление Кабинета Министров Украины об основах развития системы МВД в 1996 году. Документ не затрагивал вышеупомянутые вопросы, но вместо этого сосредоточив внимание на развитии милиции в существующих рамках. Позднее вопрос реформирования Министерства внутренних дел и милиции периодически поднимался (в 1996–1998 годах, в 2003 году, в 2005 году, в 2010 году и т. Д.) И снова опускался. Хотя в некоторых случаях некоторые изменения действительно были осуществлены, милиция все еще в значительной степени сохраняла свой централизованный характер, основанную на планах оценку эффективности и другие особенности, унаследованные от советского периода. Мы не будем пытаться подробно анализировать каждый из этих случаев; вместо этого, в этой главе мы сосредоточим наше внимание на двух более широко освещаемых случаях реформ, а именно на попытке упразднить дорожную полицию (ГАИ) в 2005 году и реформу уголовно-процессуального законодательства в 2012 году.
Sviatokum, І. Police reform in Ukraine. A reconnaissance of perceptions / Igor Sviatokum, Alexey Serdyuk and Petrus C. van Duyne // Constructing and organising crime in Europe / Petrus C. van Duyne, Alexey Serdyuk, Georgios A. Antonopoulos, Jackie H. Harvey, Klaus von Lampe (Eds.); Kharkiv National University of Internal Affairs, Northumbria University, Teesside University, Utrecht University. – Chicago-Kharkiv : Eleven International Publishing, Kharkiv National University of Internal Affairs, 2019. - P. 337-366. - DOI: https://doi.org/10.32631/ccc19.14
Keywords: Constructing and organising crime in Europe; Materials of conferences. Збірники матеріалів наукових конференцій. Сборники материалов научных конференций; Соціологія. Соціальна робота. Sociology. Social Work. Социология. Социальная работа; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; реформування; реформирование; reforming; міліція; милиция; militia; Історія. History. История; Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Кримінальний процесуальний кодекс України; Уголовный процессуальный кодекс Украины; Criminal Procedure Code of Ukraine; Державна автомобільна інспекція України; Государственная автомобильная инспекция Украины; State Automobile Inspection of Ukraine; правоохоронні органи; правоохранительные органы; law enforcement agencies